Maker movement contribution to fighting COVID‐19 pandemic: insights from Tunisian FabLabs. (5th September 2021) - Abbassi, Wyssal; Harmel, Aida; Belkahla, Wafa; Ben Rejeb, Helmi
Abstract : COVID‐19 is an unexpected and brutal pandemic that requires new innovation models to overcome the constraints of this crisis and address its multiple challenges. Open innovation does not replace a traditional closed R&D model; but in the current crisis situation, it can support an ecosystem stakeholders' effort by leveraging several collaborations. Based on the Tunisian experience, this study illustrates how a crisis can spontaneously create these collaborations between the maker's community, the users (public healthcare professionals) and key stakeholders (universities, civil society and the private sector among others). To investigate this research question, we adopted a qualitative approach based on a single embedded case study and collected data through participant observation technique. The case study describes a process of crisis‐driven innovation based on 3D printing technologies in order to provide personal protective equipment (PPE) to healthcare professionals. It highlights two distinct phases describing the evolution from a local collaborative model to the creation of a national ecosystem able to design, manufacture and address the growing need of the public healthcare system. Our findings show with empirical evidence the crucial roles played by the makers' community, FabLabs and engineers in the fight against the COVID‐19 pandemic. This study draws lessons on how a large health crisis can trigger national crisis‐driven innovation (CDI) initiatives, which helped structure the makers' network and promote collaboration towards a common national goal. A collaborative framework for CDI initiated by the Tunisian makers' community is proposed in this study and could be adopted in similar crisis contexts, in Global South and North settings.